(untitled) (Research, Society and Development, 2020)
This work has as aim at analyzing the directions of capital in Brazil and the insertion of the State in this process dialoguing with some current debates and problematizing their social and political repercussions for the workers’ struggles. It is based on a bibliographic research qualitative in its nature and supported by historical materialism framework to contribute with critical reflections on the current situation and its social effects. Within the limits of this study, priority is given to qualifying Brazil as a commodity exporter and experiencing a process of “deindustrialization” with the State collusion, and the effects which it could cause, as job decrease and insecurity. From an analysis anchored in the social relationship of capital and in the empirical reality, some aspects are listed, which indicate the need to unveil the current situation based on other parameters. It is proposed to consider the universalization of capital and the role played by the State in this sociability to avoid the risk of incurring wrong strategies of struggles. What is observed is that, in the ongoing process, the reactions by working class oscillate between conciliation and resistance, demanding to advance in the apprehension of the real to contribute to overcoming the capitalist order.